Multifocal phaeohyphomycosis caused by Exophiala xenobiotica in a kidney transplant recipient. Issue 2 (5th February 2015) - Palmisano, A.; Morio, F.; Le Pape, P.; Degli Antoni, A.M.; Ricci, R.; Zucchi, A.; Vaglio, A.; Piotti, G.; Antoniotti, R.; Cremaschi, E.; Buzio, C.; Maggiore, U.
Abstract: In recent years, black fungi have been increasingly reported as causing opportunistic infections after solid organ transplantation. Here, we report a case of insidious, relentless, and multifocal Exophiala xenobiotica infection in a kidney transplant recipient that eventually required multiple surgical excisions along with oral and intravenous antifungal combination therapy using liposomal amphotericin B and posaconazole. We compare the present case with all previously reported cases of Exophiala infection after kidney transplantation.